Sistem Pengelolaan Transaksi Pemesanan Jasa Berbasis Web Pada CV Pelita Abadi - Shafira Nurul Husna; Arie Kusumawati (UNIVERSITAS KALBIS, 2022)
Information System Of Installation Service Order in information system that supplies information for many processes that consist of customer, payment and report. Therefor, it is nedded to create an Information System Of Installation Service Order to support the company, the aim of this final project is to searching data customer, processing installation service order, payment yield more detailed report. The system development was done by data collecting, system planning, system designing, system developed ,database developed and system testing. The system programming was developed with PHP, the data base developed used MySQL and the website create with framework by Code Igniter. It can be concluded that the design and implementation on information System Information Of Installation Service Order on CV Pelita Abadi has some facilities such as customer form, service order form, and report.